Prevalence study of Echinococcus granulosus in guanaco (Lama guanicoe) from the Chilean Patagonia unexpectedly reveals the southernmost limit of Taenia omissa - Cristian A. Alvarez Rojas; Juan Francisco Alvarez; Juliana Iglesias; Anson V. Koehler; Cristian Bonacic (Parasitology)
This study presents the first detection of Taenia omissa metacestodes in guanaco (Lama guanicoe) within the Chilean Patagonia, marking the southernmost record of natural infection in an intermediate host on the continent. Taenia omissa was found in the continental part of the Magallanes region where the top predators are pumas (Puma concolor). Conversely, all metacestodes found in guanacos collected from Tierra del Fuego Island, where no pumas exist, were identified solely as Echinococcus granulosus sensu stricto. Additionally, this research highlights a tissue preference of T. omissa for liver, contrasting with E. granulosus, which predominantly affects the lungs in guanacos. We also report the infection of T. pisiformis in 1 guanaco. Our findings emphasize the need for accurate identification of metacestodes during meat inspection in an area where T. omissa and E. granulosus overlap. This research also contributes to increase the knowledge of parasite–host dynamics in wildlife and underscores the importance of considering broader spectrum intermediate hosts in the epidemiology of parasitic infections.